Older adults' online social engagement and social capital: the moderating role of Internet skills. Issue 7 (19th May 2022) - Nguyen, Minh Hao; Hunsaker, Amanda; Hargittai, Eszter
ABSTRACT: The emergence of social network sites and online communities has offered new possibilities for older adults to stay socially connected and older adults comprise a growing user group of social media. This paper examines the relationship between older adults' online social engagement and social capital based on a national survey of adults aged 60 and over. Findings show that older adults who engage more often in specific online social activities (i.e., asking questions on social media, looking at photos of family members/others) enjoy greater bridging social capital (both in offline and online contexts) than those who do so less often. Furthermore, Internet skills moderate the relationship between online social engagement and social capital. Specifically, older adults with greater Internet skills benefit relatively more from engaging in specific online social activities more often with respect to online bridging. The paper discusses the implications for digital inequality scholarship.